Cytosolic Abnormally Hyperphosphorylated Tau But Not Paired Helical Filaments Sequester Normal MAPs and Inhibit Microtubule Assembly - Iqbal, Khalid (2008)
Neurofibrillary degeneration of abnormally hyperphosphorylated tau, a hallmark of Alzheimer's disease (AD) and related tauopathies, occurs both as cytosolic aggregated/oligomeric protein (AD P-tau) and as neurofibrillary tangles. The abnormal hyperphosphorylation not only results in the loss of tau function of promoting assembly and stabilizing microtubules but, in the case of the cytosolic AD P-tau, also in a gain of a toxic function whereby the pathological tau sequesters not only normal tau, but also the other two neuronal microtubule associated proteins (MAPs), MAP1A / MAP1B and MAP2, and causes inhibition and disruption of microtubules. The sequestration of normal MAPs leads to a slow but progressive degeneration of the affected neurons. The affected neurons defend against the toxic tau by continually synthesizing new normal tau as well as by packaging the abnormally hyperphosphorylated tau into polymers, i.e., neurofibrillary tangles of paired helical filaments, twisted ribbons and straight filaments. The filamentous tau is inert; it neither interacts with tubulin and stimulates it assembly, nor binds to normal MAPs and causes disruption of microtubules. These findings suggest the inhibition of tau abnormal hyperphosphorylation and not the aggregation of tau as the preferred therapeutic target for AD and related tauopathies.